2021
DOI: 10.3390/nu13020317
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Factors Associated with Levels of Fatty Acids, Specifically n-3 PUFA during Pregnancy: ECLIPSES Study

Abstract: An optimal fatty acid (FA) profile during pregnancy, especially docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), is essential for the health of the mother and child. Our aim was to identify the socioeconomic and maternal lifestyle factors associated with serum FA concentration in pregnant women. A longitudinal study was conducted on 479 pregnant women, who were assessed during the first (T1) and third (T3) trimesters of pregnancy. Data on maternal characteristics, food consumption, and lifestyle wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 58 publications
(114 reference statements)
2
28
0
Order By: Relevance
“…These are rich dietary sources of MUFA, especially OL of high oxidative stability and beneficial health influence. A similar tendency concerning olive oil was observed by Aparicio et al [ 18 ]. High usage of sunflower oil, also established in the present study, especially for frying, seems disquieting due to its lower oxidative stability resulting from high LA content, etc.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These are rich dietary sources of MUFA, especially OL of high oxidative stability and beneficial health influence. A similar tendency concerning olive oil was observed by Aparicio et al [ 18 ]. High usage of sunflower oil, also established in the present study, especially for frying, seems disquieting due to its lower oxidative stability resulting from high LA content, etc.…”
Section: Discussionsupporting
confidence: 88%
“…Our previous results clearly indicated that proper CLA supply in the maternal diet may beneficially influence children’s health also in adulthood [ 1 , 20 , 21 ]. Maternal serum fatty acids profile generally was similar to that revealed in studies by other authors [ 18 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…To determine the benefit for maternal-child health of maintaining an optimal fatty acid (FA) profile during pregnancy, Aparicio et al [ 5 ] studied the environmental factors that were related to levels of saturated FA, monounsaturated FA and omega 3 and omega 6 polyunsaturated FA at the beginning and end of pregnancy in a sample of healthy pregnant women from the Spanish Mediterranean area (ECLIPSES study). Adjusted multivariate analyses for several maternal factors (educational level, age, BMI, smoking, alcohol consumption, physical activity, food consumption) showed that higher educational levels, older age, greater consumption of fish and shellfish, and/or not smoking during pregnancy were associated with higher concentrations of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and consequently the indices for n-6/n-3 and arachidonic acid (AA)/EPA were reduced.…”
mentioning
confidence: 99%